Modelling and optimization of a machine production process: Buffer stock supply implementation and replenishment control - Elbaraka Saad; Mokhlis Salah-eddine; Barra Adil; Fouraiji Hicham (E3S Web of Conferences)
In the industry and logistic the production process is the sequence that aims to convert raw materials into finished or semi-finished products. It is identified as one of the most complex phases of the supply chain due to its close interdependence with other processes such as replenishment. In this perspective, the efficiency of the manufacturing process essentially relies on the decisions of the responsible operators for supplying machines with raw materials. These decisions do not ensure optimal operation efficiency. This document proposes a scientific study based on the modelling and control of the production process in a smart industry perspective. Initially, one will present a modelling of the manufacturing system conceptualized as an industrial machine, as well as the replenishment policy, that will be conceived as a control loop tuning the raw material supplies quantities into the production machine following a proposed architecture. We will then proceed to simulate this scenario using the Simulink interface to identify the most influential parameters and improve them.